Linguistic Signs of The Symbolic Meaning in Tabuik Pariaman West Sumatra - Amelia Yuli Astuti; Suci Rahmadani (Fakultas Sastra Universitas Ekasakti, 2023)
This research is entitled linguistic on the meaning of tabuik symboik in Pariaman, West Sumatra. It explains the sign of the linguistic meaning of pen and Omen, denotative and connotative meaning on Tabuic symbols. It aims to improve the order of pens and signs and enhance the denotative and connotative meanings in Tabuic symbols. Based on these sources, the data were collected by observation method with interview and photo techniques. The analysis is carried out by semiotics, signs of linguistic meaning and the sequence of presentation methods. The Data were analyzed by associating them with concepts discovered by Chandler (2007).Saussure's theory was to classify the pen and the mark.Chandler's theory is to classify denotative and connotative meanings. The analysis results are presented descriptively. After analyzing the data, it was found that there are several specifications of the meaning of the Tabuik symbol. This research shows that the Tabuik symbol has a high cultural and religious meaning and value, especially in Pariaman . Tabuik has the form of a sign and a sign and the meaning we can see from the form and symbol of Tabuik.